Mixed eccentricity fault detection based on stator current analysis in line start permanent magnet synchronous motor - Karami, Mahdi (2015)
A detection strategy for three-phase, 4-po1e LSPMSM under mixed eccentricity fault through motor current signature analysis (MCSA) is proposed in this investigation. An experimental test rig is provided to integrate different steps of designed methodology in order to sample the stator current signal of case study motor at the given rates under several operation conditions. Low degree of mixed eccentricity with 17% static and 17% dynamic eccentricity is developed to identify the efficient fault-related components at specific frequencies with the capability of fault detection at early stages. Mixed eccentricity degrees are increased with 33% dynamic and 17% static eccentricity as well as 33% static and 17% dynamic eccentricity where it is also provided to evaluate the effects of static and dynamic eccentricity on the harmonic components pertaining to mixed eccentricity. Effect of mechanica110ad on mixed eccentricity fault detection in LSPMSM is investigated via change the load levels from 0% to 100% within six steps in the condition monitoring process. A simulation study based on finite element method (FEM) is carried out using the real parameters and practical conditions such as motor design parameters, mixed eccentricity degrees and load levels in order to derive the efficient results for eccentricity detection process. Current spectrum of case study motor under 17% static and 17% dynamic eccentricity is investigated and it is indicated that the amplitudes of fault-related components at rotor frequency 25 Hz increased by 18% in experimental results and 13.2% in the numerical evaluation which are the highest incremental rate in comparison with the components of third and fifth harmonics of rotor frequency i.e. 75 Hz and 125 Hz. Further increase of dynamic eccentricity degree by 33% at fixed static eccentricity degree of 17% leads to raise the amplitudes of mixed eccentricity-related harmonic components at 25 Hz, 75 Hz and 125 Hz by 26.6%, 12.7% and 5.4% respectively. While the degree of static eccentricity is increased to 33% at fixed degree of dynamic eccentricity 17%, the incremental variation in the amplitudes of harmonic components at 25 Hz, 75 Hz and 125 Hz is 15.5%, 12.7% and 1.8%, respectively. lt is derived that mixed eccentricity fault generates harmonic components at 25 Hz, 75 Hz and 125 Hz in the stator current of LSPMSM while the amplitudes of these harmonic components increase proportional to fault severity. Furthermore, the effect of dynamic eccentnclty on the aforementioned harmonic components is superior to static eccentricity. Increase the level of mechanical load in LSPMSM result in reduces the amplitudes of harmonic components related to mixed eccentricity while these amplitudes increase upon the progress of fault degree for fixed load. Accordingly,mixed eccentricity fault in LSPMSM is scrutable only in the fixed levels of load.